Health, eating, and 'healthy eating' : how New Zealand pakeha 'key kitchen people' relate food and wellbeing : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Anthropology at Massey University, Albany, New Zealand - Russell, Samantha (Massey University, 2010)
Food practices and health are complex cultural constructions. In Western cultures people construct and negotiate them with reference to a variety of health messages, experiences, and strategies for coping with the plethora of food choices they must make daily. Beliefs about food and health are important both for understanding people and cultures, and for applied reasons such as providing culturally appropriate and effective healthcare and advice. In New Zealand ideas of 'health' are increasingly linked to ideas about food and eating through media and medical discourses and everyday conversation, making an exploration of these ideas timely and relevant. This thesis focuses on ‘Key Kitchen People’ (people who are the main food shoppers and preparers for their household, after Douglas, 1973), how they conceive of ‘health’, and what this means for the types of food they choose. Eight face-to-face, oneon- one, semi-structured interviews were conducted, along with observations of participants’ pantries and fridges and discussions about their contents with regard to participants’ conceptions of food-health connections. This project focuses on non[-]problematic eating and health and does not deal with eating disorders, weight problems, or chronic disease. Instead, I discuss how health is thought about, how food and health are connected, and how Key Kitchen People deal with the food anxiety this creates. The research demonstrates that ‘health’ is socially and personally constructed with reference to values, health messages, bodily feedback, and experience, and that food is inextricably connected to individuals’ health experiences and conceptions. Because food was linked with health, participants also expressed feeling some anxiety over the foods they chose to eat, but coped with this by using ‘common sense’ and ‘rules of thumb’. The life practices that participants employed with reference to their ideas about health resulted in a range of negotiations between various tensions they encounter (for example, in relation to ideas about nutrition, processes of control and release, anxiety and risk, personal experience and received health messages) that both effect, and result from, connecting food with health. Participants created their own truths in the face of these complex and often contradictory discourses. In a society supposedly controlled by corporations and media, health, food, and eating are remarkably improvised and personal constructions.
Keywords: Food; Health; Food-health connections; Food practices; Food choice; Health as a social construction; Food anxiety; Food choice coping strategies; Nutritionism; Rules of thumb